GaN phosphors converted white light‐emitting diodes for high luminous efficacy and improved thermal stability. Issue 4 (1st August 2020) - Kumar, Mirgender; Sunny; Kumar, Anuj; Seong, Kwang-Su; Park, Si-Hyun
Abstract : This study analysed GaN nanophosphors based white light‐emitting diodes (WLEDs) with ultraviolet (UV) excitation. Graphene quantum dots (GQDs) used as a charge transfer medium to enhance the performance in terms of luminous efficacy and colour quality. The improvement in colour rendering and colour temperature has been observed with the increase in injection current. The luminous efficacy of radiation also gets improved with injection current and maximises up to 255 lm/W at 260 mA along with 90 colour rendering index and 7100 K correlated colour temperature. Mapping of higher surface temperature for GQD‐based devices shows a better thermal stability, indicating the good heat dissipation capability of GQDs because of excellent thermal conductivity. Therefore, proposed WLEDs were found more competent with improved thermal quenching of phosphors for rare‐earth‐free solid‐state lighting as compared to the blue chip‐excited yellow phosphors.